The Students’ and Parents Voices on Online Learning in SMP Wahid Hasyim Pasuruan - Lilik Inawati; Lestari Setyowati (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2020)
The pandemic of COVID 19 has caused a drastic change in the way the students’ learn. Instead of learning at school, the students learn from home.  This paper is aimed at describing the students’ and parents’ opinion, reasons, and difficulties  during the learning from home. The researcher used a mixed method design to collect the data. The subjects of the study were 25 students in grade 9 of SMP A Wahid Hasyim Pasuruan and 28 parents. The instruments were open and close questionnaire and interview. The data is collected from October  to December 2020. The result shows that 1) the students and the parents agreed that online learning was effective for the teaching and learning process  during the pandemic of COVID 19. 2)  The students like online learning because  online learning saves time (41.66%). On the other hand, the parents prefer online learning because of health reasons, which is  to avoid the spread of covid-19.  The major problem faced by the students and parents  is the internet quota.  The result shows that most students and parents agree that online learning becomes the  most preferable way to conduct the teaching and learning process during the pandemic of COVID 19.